2017
DOI: 10.1136/heartjnl-2017-311233
|View full text |Cite
|
Sign up to set email alerts
|

Revascularisation compared with initial medical therapy for non-ST-elevation acute coronary syndromes in the elderly: a meta-analysis

Abstract: Routine invasive therapy reduces MI and repeat revascularisation and may reduce mortality at the expense of major bleeding in elderly patients with NSTEACS. Our findings highlight the need for further RCTs to better determine the effect on mortality and contemporary bleeding risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
3
20
1
Order By: Relevance
“…A meta-analysis that pooled these data, published in 2017, did not find clear evidence that invasive management reduced long-term mortality (OR 0·84, 95% CI 0·66–1·06; p=0·15). 28 Interpretation is difficult because TACTICS-TIMI 18 compared an early invasive with a selective invasive strategy with predischarge ischaemia test, following which 49% of patients underwent coronary catheterisation and 32% had revascularisation. 26 Similarly, the FIR trials, which reported cardiovascular mortality but not all-cause mortality, compared an invasive strategy with a selective invasive strategy, which involved a predischarge ischaemia test, following which nearly half of patients had revascularisation during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis that pooled these data, published in 2017, did not find clear evidence that invasive management reduced long-term mortality (OR 0·84, 95% CI 0·66–1·06; p=0·15). 28 Interpretation is difficult because TACTICS-TIMI 18 compared an early invasive with a selective invasive strategy with predischarge ischaemia test, following which 49% of patients underwent coronary catheterisation and 32% had revascularisation. 26 Similarly, the FIR trials, which reported cardiovascular mortality but not all-cause mortality, compared an invasive strategy with a selective invasive strategy, which involved a predischarge ischaemia test, following which nearly half of patients had revascularisation during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease (CAD) remains a leading cause of morbidity and mortality in older populations. 1,2 Coronary computed tomography angiography (CCTA)-identified non-obstructive and obstructive CAD are both associated with increased major adverse cardiovascular outcomes (MACE) and all-cause mortality. 3 Moreover, atherosclerotic disease burden quantified by either an increasing number of obstructed vessels (single-, double-, triple-vessel, and/or left main) or by the number of coronary segments manifesting atherosclerotic plaque correlate directly with MACE at both medium-and long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of coronary artery disease is common in patients over the age of 75 years of age especially within the context of acute coronary syndromes. Careful consideration of the treatment strategy for acute coronary syndromes in this age group is particularly important in view of their increased complexity, complication rate and hospitalisation [6]. In this review, we will briefly discuss the history of percutaneous coronary intervention and then focus on the use of drug-coated balloons giving particular emphasis on their use in de-novo lesions and in the elderly.…”
Section: Introductionmentioning
confidence: 99%